2005
DOI: 10.1371/journal.pgen.0010064
|View full text |Cite
|
Sign up to set email alerts
|

Medical Sequencing of Candidate Genes for Nonsyndromic Cleft Lip and Palate

Abstract: Nonsyndromic or isolated cleft lip with or without cleft palate (CL/P) occurs in wide geographic distribution with an average birth prevalence of 1/700. We used direct sequencing as an approach to study candidate genes for CL/P. We report here the results of sequencing on 20 candidate genes for clefts in 184 cases with CL/P selected with an emphasis on severity and positive family history. Genes were selected based on expression patterns, animal models, and/or role in known human clefting syndromes. For seven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
216
3
21

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 235 publications
(262 citation statements)
references
References 61 publications
(48 reference statements)
11
216
3
21
Order By: Relevance
“…Of these variants, only the P147Q variant, which has been detected in a number of Southeast Asian populations, is a relatively common variation in the MSX1 gene. In addition to the present study, this variant has been detected in three Vietnamese families, 17 two Filipino families 9 and three Thai families. 26 The prevalence of this variant may reflect a Founder effect in these populations.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Of these variants, only the P147Q variant, which has been detected in a number of Southeast Asian populations, is a relatively common variation in the MSX1 gene. In addition to the present study, this variant has been detected in three Vietnamese families, 17 two Filipino families 9 and three Thai families. 26 The prevalence of this variant may reflect a Founder effect in these populations.…”
Section: Discussionsupporting
confidence: 68%
“…Consistent with the present study, it has been detected across affected and non-affected members of the same family and in unrelated healthy controls. 9,17,26 Although this variant is located within a conserved phosphorylation motif within the MH3 domain, 23 it is revealed that it may not be pathogenic. 26 Therefore, it, at best, may contribute to clefting with other genetic and environmental risk factors in a complex inheritance pattern.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive studies in knockout mice have also demonstrated that Msx1-Bmp signaling, regulating expression of Shh, is essential for palate development (Zhang et al 2002) and the identiWcation of a MSX1 stop mutation in a Dutch family with a combination of tooth agenesis and OFC conWrmed MSX1 as a candidate gene for clefting in humans (van den Boogaard et al 2000). Sequencing-and association studies have indicated a role for MSX1 in the etiology of nonsyndromic orofacial clefting (Lidral et al 1998;Beaty et al 2001;Blanco et al 2004;Fallin et al 2003;Jezewski et al 2003;Jugessur et al 2003;Vieira et al 2003;Moreno et al 2004;Vieira et al 2005;Modesto et al 2006;Tongkobpetch et al 2006;Park et al 2007), although results published by others question this role (Mitchell et al 2001;Koillinen et al 2003;Etheredge et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Estudos examinando o padrão de recorrência das fissuras não-sindrômicas estimam que cerca de 3 a 14 genes possam estar envolvidos na determinação desse fenótipo (SCHLIEKELMAN; SLATKIN, 2002;RILEY et al, 2007;VIEIRA , 2008a). Estudos de ligação e associação têm indicado alguns genes candidatos, dentre eles: TGFA, TGFB2, TGFB3, FGF, FOXE1, GLI2, JAG2, LHX8, SATB2, SKI, ERBB2, SPRY2, TBX10, MSX 2, MSX1 e IRF6 (MURRAY, 1995;JEZEWSKI et al, 2003;BLANTON et al, 2005;VIEIRA et al, 2005;VIEIRA, 2008a;VIEIRA et al, 2008b;VIEIRA et al, 2008d;TANG et al, 2009;MARAZITA et al, 2009;JUGESSUR et al, 2009;SULL et al, 2009 ZUCCHERO et al, 2004;RILEY et al, 2007;VIEIRA, 2008a).…”
Section: T T E E R R a A T T U U R R A Aunclassified